2009
DOI: 10.3748/wjg.15.5586
|View full text |Cite
|
Sign up to set email alerts
|

Unsedated transnasal small-caliber esophagogastroduodenoscopy in elderly and bedridden patients

Abstract: AIM:To evaluate the safety of unsedated transnasal small-caliber esophagogastroduodenoscopy (EGD) for elderly and critically ill bedridden patients. METHODS:One prospective randomized comparative study and one crossover comparative study between transnasal small-caliber EGD and transoral conventional EGD was done (Study 1). For the comparative study, we enrolled 240 elderly patients aged > 65 years old. For the crossover analysis, we enrolled 30 bedridden patients with percutaneous endoscopic gastrostomy (PEG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…However, the load of the endoscopic examinations may constitute a risk for rupture of the aortic aneurysm. Transnasal small caliber endoscopy is a safer procedure than transoral conventional endoscopy particularly in terms of cardiopulmonary effects (11,12). Therefore, for the management of patients suspected of having AEFs, transnasal endoscopy is considered after CT.…”
Section: Discussionmentioning
confidence: 99%
“…However, the load of the endoscopic examinations may constitute a risk for rupture of the aortic aneurysm. Transnasal small caliber endoscopy is a safer procedure than transoral conventional endoscopy particularly in terms of cardiopulmonary effects (11,12). Therefore, for the management of patients suspected of having AEFs, transnasal endoscopy is considered after CT.…”
Section: Discussionmentioning
confidence: 99%
“…Trans-nasal endoscopy can usually be performed comfortably due to attenuation of the gag reflex [22]; indeed in Japan, trans-nasal endoscopy is a very common procedure and can be performed without sedation. It has also been reported that trans-nasal endoscopy is less invasive than other techniques with respect to the cardiopulmonary function [23][24].…”
Section: Discussionmentioning
confidence: 99%
“…In most comparative studies, transnasal EGD was found to have smaller cardiovascular impacts than transoral conventional EGD, and transnasal EGD was found to be safer than conventional EGD for most patients (20,21,29). Transnasal small caliber EGD was reported to be a safer method than transoral conventional EGD in aged hypertensive patients or critically ill, bedridden patients who are undergoing percutaneous endoscopic gastrostomy (PEG) feeding (30,31). The explanation behind these results can be attributed to less sympathetic stimulation induced by transnasal small caliber EGD leading to lesser elevation of blood pressure and pulse (5).…”
Section: Safetymentioning
confidence: 99%
“…It is known that the transoral conventional endoscope may stimulate salivary secretion and further increase the risk of aspiration. In one study, unsedated transnasal small caliber EGD in elderly and bedridden patients was found to be much safer than its transoral counterpart with conventional endoscopes with regard to the risk of aspiration pneumonia (31). Application of this technique was also reported to be a safe and tolerable technique in the diagnosis of hypopharyngeal cancer and screening of simultaneous esophageal cancer (26).…”
Section: Safetymentioning
confidence: 99%